MODELING OF VOLATILITY OF INTEREST AND TREASURY BILL RATES USING ARCH / GARCH FAMILY MODELS AND THEIR EFFECT ON PENSION FUND (International Journal of Engineering Sciences & Management Research, 2017)
Frequent fluctuations in interest rates often affect purchasing power of citizens and many businesses. Prices of commodities rise upwards very fast in most cases but take time drop. If these fluctuations are predicted early enough, probably measures can be taken in advance to deal with these shocks before the prices of commodities change. In this study we model the volatility of interest rates and Treasury bill rates using GARCH family models and asses how each of them affect the growth of pension fund. The interest and Treasury bill rates were converted into simple returns and modeled by use of ARCH and GARCH (1, 1) models. The GARCH(1, 1) was preferred because it allows many parameters and considers conditional heteroscedasticity of data to assess volatility of interest rates and Treasury bill rates. Volatility measures the errors made in modeling returns. It was discovered that the average volatility is not constant but varies with time and can be forecast or predicted in both cases. A multifactor modelwas used to investigate how each affect pension Fund, it was revealed that interest rates affected pension fund more than the Treasurybill rates, and the model can be used to project growth of the fund.